Effects of storage conditions and digestion time on DNA amplification of 1 biting midge (Culicoides) blood meals - Bellekom, B; Bailey, A; England, M; Langlands, Z; Lewis, OT; Hackett, TD (BioMed Central, 2023)
Background Molecular analysis of blood meals is increasingly used to identify the hosts of biting insects such as midges and mosquitoes. Successful host identification depends on the availability of sufficient host DNA template for PCR amplification, making it important to understand how amplification success changes under different storage conditions and with different durations of blood meal digestion within the insect gut before being placed into the storage medium.